2019
DOI: 10.1111/jgs.15799
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Palliative Care Champions to Promote High‐Quality Care to Those with Serious Illness

Abstract: Leading medical authorities advocate for routine integration of palliative care for all major causes of death in the United States. With rapid growth and acceptance, the field of palliative care is tasked with addressing a compelling question of its time: "Who will deliver timely, evidence-based palliative care to all who should benefit?" The current number of palliative care specialists will not suffice to meet the needs of persons with serious illness. In 2010, initial estimates quantified the shortage at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The results of this study reveal that both available time and organisation of the palliative care team constrains the function of the resource nurse. Kamal et al (12) , in the context of hospitals, stated that implementing a care champion network to improve quality requires system changes as well, eg allocating necessary time to talk with the serious ill patients about goals of care. The results showed that support from the ward nurse, and mutual trust between ward nurse and resource nurse is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study reveal that both available time and organisation of the palliative care team constrains the function of the resource nurse. Kamal et al (12) , in the context of hospitals, stated that implementing a care champion network to improve quality requires system changes as well, eg allocating necessary time to talk with the serious ill patients about goals of care. The results showed that support from the ward nurse, and mutual trust between ward nurse and resource nurse is important.…”
Section: Discussionmentioning
confidence: 99%
“…The resource nurse is also supposed to work with system improvements related to routines, procedures and pathways, in addition to advising and guiding colleagues, disseminating new knowledge and initiating re ection (8). Parallel terms for the resource nurse in the Norwegian context are, in the international literature, the palliative resource nurse (10), link nurse (11) or palliative care champion (12).…”
Section: Introductionmentioning
confidence: 99%
“…A PC champion is a clinician who is interested in PC, has been trained to skillfully assess and manage patients' PC needs, and promotes the learning and use of PC skills (e.g., communication) as part of standard practice within their own specialty. 35 In a population-based PC delivery system, champions can play a critical role in closing gaps in care for patients with serious illness.…”
Section: Tip 6: Clinical Decision Support Tools Can Help To Further Tmentioning
confidence: 99%
“…Palliative care delivery comes in 3 levels: primary, champion, and specialty. 13 Primary palliative care is the common, fundamental palliative care delivered by every clinician to every patient with serious illness. It comprises basic symptom management and goal setting by which primary and specialty clinicians (eg, cardiologists, oncologists) are experienced and comfortable.…”
Section: F R O N T I E R S O F C a R Ementioning
confidence: 99%